Direct reactions with the AT-TPC - Ayyad, Yassid; Bazin, Daniel; Bonaiti, Francesca; Chen, Jie; Li, Xiaobin; Anthony, Adam; Avila, Melina; Beceiro-Novo, Saul; Bhatt, Khushi; Cabo, Cristina; Furuno, Tatsuya; Guimarães, Valdir; et al. (Frontiers in Physics, 2025)
IntroductionDirect reactions are crucial tools for accessing properties of the atomic nucleus. Fundamental and exotic phenomena such as collective modes, pairing, weakbinding effects and evolution of single-particles energies can be investigated in peripheral collisions between a heavy nucleus and a light target. The necessity of using inverse kinematics to reveal how these structural properties change with isospin imbalance renders direct reactions a challenging technique when using the missing mass method.MethodsIn this scenario, Active Target Time Projection Chambers (AT-TPC) have demonstrated an outstanding performance in enabling these types of reactions even under conditions of very low beam intensities. The AT-TPC of the Facility for Rare Isotope Beams (FRIB) is a next generation multipurpose Active Target. When operated inside a solenoidal magnet, direct reactions benefit from the measurement of the magnetic rigidity that enables particle identification and the determination of the excitation energy with high resolution without the need of auxiliary detectors. Additionally, the AT-TPC can be coupled to a magnetic spectrometer improving even further its spectroscopic investigation capability.ResultsIn this contribution, we discuss inelastic scattering and transfer reaction data obtained via the AT-TPC and compare them to theory. In particular, we present the results for the 14C(p,p′) and 12Be (p,d)11Be reactions.DiscussionFor 14C, we compare the experimental excitation energy of the first 1– excited state with coupled-cluster calculationsbased on nuclear interactions from chiral effective field theory and with available shell-model predictions. For 12Be, we determine the theoretical spectroscopic factors of the 12Be (p,d)11Be transfer reaction in the shell modeland compare them to the experimental excitation spectrum from a qualitative standpoint.